2000
DOI: 10.1007/s100380050200
|View full text |Cite
|
Sign up to set email alerts
|

The 4G/5G polymorphism of the plasminogen activator inhibitor-1 gene is associated with severe preeclampsia

Abstract: Preeclampsia is associated with thrombosis of the intervillous or spiral artery. A deletion/insertion polymorphism (4G or 5G) in the promoter of the plasminogen activator inhibitor type 1 (PAI-1) gene is suggested to be involved in regulating the synthesis of the inhibitor, 4G allele, being associated with the enhanced gene expression and plasma PAI-1 levels. We assessed the association between preeclampsia and the 4G/5G polymorphism of the PAI-1 gene in 115 preeclamptic patients, 210 pregnant controls, and 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 24 publications
3
39
1
5
Order By: Relevance
“…The -675 4G allele determines increased PAI-1 concentration and enhanced prothrombotic activity. The -675 4G/5G polymorphism has been suggested to be involved in the etiology of intrauterine fetal death, intrauterine growth restriction, preterm placental abruption, recurrent miscarriage, and preeclampsia [20,21].…”
Section: -675 4g/5g Pai-1 Gene Polymorphismmentioning
confidence: 99%
“…The -675 4G allele determines increased PAI-1 concentration and enhanced prothrombotic activity. The -675 4G/5G polymorphism has been suggested to be involved in the etiology of intrauterine fetal death, intrauterine growth restriction, preterm placental abruption, recurrent miscarriage, and preeclampsia [20,21].…”
Section: -675 4g/5g Pai-1 Gene Polymorphismmentioning
confidence: 99%
“…10 Other chromosomal regions that have showed suggestive linkage include 4, 11 2q23, 8 11q23-24, 10 7q36, 12 12q, 3p, 15q, 10q, and 22q. 13 In parallel, association studies have suggested the involvement of candidate genes in susceptibility to preeclampsia, mostly related to oxidative stress, vasoactive substances, and coagulation disorders: lipoprotein lipase (LPL), 14 5-10 methylenetetrahydrofolate reductase (MTHFR), 15 glutathione-S transferase pi (GSTP1), 16 factor V (F5), 15,17 apolipoprotein E (APOE), 18 plasminogen activator inhibitor-1 (SERPINE1), 19 microsomal epoxide hydrolase 1 (EPHX1), 20 endothelial nitric oxide synthase (NOS3), 21 angiotensinogen (AGT), 22 and tumor necrosis factor-␣ (TNF). 23 Essential hypertension is an elusive disease.…”
mentioning
confidence: 99%
“…Можно предполагать, что удельный вклад данного полиморфиз-ма в возникновении осложнений беременности в разных популяциях может значительно варьировать. Действи-тельно, для большинства европейских стран, как и для Японии, были выявлены положительные ассоциации между полиморфизмом в гене Pai1 и риском возникно-вения акушерских осложнений (Fabbro et al, 2003;Hakli et al, 2003;Wiwanitkit, 2006, Yamada et al, 2000. По всей вероятности данный полиморфизм можно отнести к самостоятельным факторам риска осложнений беремен-ности.…”
Section: Discussionunclassified